Potential correlation between anti-laminin 332 autoantibodies and malignant tumours in anti-BP180-type mucous membrane pemphigoid - Li, Xiaoguang; Pas, Hendri H; Qian, Hua; Rashid, Hanan; Horvath, Barbara; Yilmaz, Osman K.; Beek, Nina van; Schmidt, Enno; Zillikens, Detlef; Ishii, Norito; Tsuruta, Daisuke; Hashimoto, Takashi (Clinical and experimental dermatology, 2024)
Dear Editor, Several studies have indicated a correlation between the presence of malignant tumours and anti-laminin 332 (LM332)-type mucous membrane pemphigoid (MMP),1,2 in contrast to the absence of such a correlation in patients with anti-BP180-type MMP (BP180-MMP).3 It has been observed that anti-LM332 autoantibodies may also be present in patients with BP180-MMP.3 In the present study, we assessed the relationship between anti-LM332 autoantibodies and the incidence of malignant tumours in patients with BP180-MMP.We recruited 520 patients with BP180-MMP, including 331 patients from Japan, 19 from China, 108 from the Netherlands and 62 from Germany. Essential criteria for BP180-MMP diagnosis include reactivity with the epidermal side in indirect immunofluorescence using 1 M NaCl split skin, positivity for anti-BP180 autoantibodies in immunoblotting of epidermal extract, and/or immunoblotting and/or enzyme-linked immunosorbent assay of recombinant proteins of BP180 NC16a and/or C-terminal domains. The detection of anti-LM332 autoantibodies was conducted utilizing various methods among multiple cohorts: by immunoblotting of purified LM332 or its recombinant protein in the Japanese and Chinese cohorts;1,3 by keratinocyte footprint assay in the Dutch cohort;4 by indirect immunofluorescence (Biochip® Mosaic; EUROIMMUN, Lübeck, Germany)2,4 and immunoblotting of keratinocyte-derived LM332 in the German cohort.